2019
DOI: 10.3390/molecules24071195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu/Mn-Fortification on In Vitro Activities of the Peptic Hydrolysate of Bovine Lactoferrin against Human Gastric Cancer BGC-823 Cells

Abstract: Bovine lactoferrin hydrolysate (BLH) was prepared with pepsin, fortified with Cu2+ (Mn2+) 0.64 and 1.28 (0.28 and 0.56) mg/g protein, and then assessed for their activity against human gastric cancer BGC-823 cells. BLH and the four fortified BLH products dose- and time-dependently had growth inhibition on the cells in both short- and long-time experiments. These samples at dose level of 25 mg/mL could stop cell-cycle progression at the G0/G1-phase, damage mitochondrial membrane, and induce cell apoptosis. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Several peptides from natural food hydrolysates have aroused some researchers' great interest; among these assessed proteins is lactoferrin (LF) that exists in milk and dairy foods. Previous studies had proposed that both LF and a LF derivative lactoferricin B had in vitro anti-cancer activities against two gastric cancer SGC-7901 and AGS cells [8,10]; their results also proved that both LF and lactoferricin B had pro-apoptosis to the cells. Recently, researchers have also paid special attention to the potential interaction between proteins and other dietary components.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several peptides from natural food hydrolysates have aroused some researchers' great interest; among these assessed proteins is lactoferrin (LF) that exists in milk and dairy foods. Previous studies had proposed that both LF and a LF derivative lactoferricin B had in vitro anti-cancer activities against two gastric cancer SGC-7901 and AGS cells [8,10]; their results also proved that both LF and lactoferricin B had pro-apoptosis to the cells. Recently, researchers have also paid special attention to the potential interaction between proteins and other dietary components.…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, lactoferrin upon being hydrolyzed by pepsin will yield the important product lactoferricin B, which has been proved to cause cell apoptosis in two gastric cancer cells [5,6]. A previous study of our group also indicated that fortified metal (Cu 2+ or Mn 2+ ) lactoferrin hydrolysates were responsible for apoptosis of AGS and BGC cells [7,8].…”
Section: Introductionmentioning
confidence: 87%
“…Then Lf-LP-DTX and RGD-Lf-LP-DTX were prepared [ 3 ]. Lf grafting rate was determined by the BCA assay kit [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Of particular interest is the in vivo observation that Zey effectively inhibited tumor growth in nude BALB/c mice bearing BGC823 xenografts without any evident cytotoxic effects [18]. Bo et al have investigated the anticancer activity of bovine lactoferrin hydrolysate (BLH) with added Cu 2+ and Mn 2+ on human gastric cancer BGC-823 cells [19]. They showed that the fortified BLH products had higher activities than BLH alone as evidenced by induction of apoptosis and activation of the classic caspase-3-dependent apoptotic pathway [19].…”
mentioning
confidence: 99%
“…Bo et al have investigated the anticancer activity of bovine lactoferrin hydrolysate (BLH) with added Cu 2+ and Mn 2+ on human gastric cancer BGC-823 cells [19]. They showed that the fortified BLH products had higher activities than BLH alone as evidenced by induction of apoptosis and activation of the classic caspase-3-dependent apoptotic pathway [19]. As opposed to the use of single purified molecules, several studies have highlighted the anticancer effects of plant-derived fractions and/or extracts on different cell models.…”
mentioning
confidence: 99%